(untitled) (Szociológiai Szemle, 2024)
This article is a part of a comprehensive research conducted by the author on the history of the residents of a building in Budapest by means of the method of "Oral History". In this paper the history of a Christmas Eve is being described whereby the audience learn to know the characters, their past and their internal relations through their discussions. The event was recorded on video. Therefore it was possible to evaluate the contribution of the method of using video and in a broader sense applying visual materials when conducting a sociological research.